Form Against Content: René Girard's Theory of Tragedy - Gans, Eric Lawrence (Revista portuguesa de filosofia, 2000)
Tragedy is the most openly sacrificial of literary forms. In contrast to his theory of the novel as a lucid revelation of the truth of mimetic desire, René Girard understands tragedy as an only partial deconstruction of sacrificial myth. But while Girard's radical formalism provides a necessary anthropological insight, it evacuates the esthetic experience provided by tragedy. A more fruitful approach is suggested by the common source of the arbitrariness of the sacrificial victim and the arbitrary nature of the linguistic sign in the originary linguistic event. Art requires us to participate in the content of the esthetic sign and as a consequence not merely to motivate the sacrificial form of the artwork but to desire it not to be realized. This acceptance of sacrificial arbitrariness is shown, in conclusion, to be characteristic of the novel as well as of tragedy. La tragédie est la forme littéraire de toutes la plus sacrificielle. Pour René Girard, la tragédie est la déconstruction nécessairement partielle d'un mythe sacrificiel, à la différence du roman qu'il considère comme une révélation lucide de la vérité du désir mimétique. Mais malgré la lumière anthropologique essentielle fournie par le formalisme radical de Girard, celui-ci évacue l'expérience esthétique de la tragédie. Une approche plus fructueuse est suggérée par la source commune de l'arbitraire du choix de la victime sacrificielle et de l'arbitraire du signe linguistique dans l'événement originaire du langage. En nous obligeant à participer au contenu du signe esthétique, l'art nous requiert non seulement de motiver la forme sacrificielle de l'œuvre d'art mais de désirer en même temps qu'elle ne se réalise pas. En conclusion, il est montré que l'assomption de l'arbitraire sacrificiel existe autant dans le roman que dans la tragédie.